Novel shape memory materials - Chan, Lester Huang Boon. (2011)
In this report, the feasibility of new types of novel shape memory hybrids (SMH) and materials were investigated. This is a more extensive research based on the silicone based thermo-responsive shape memory hybrid that was first investigated by Mr. Yap Soon Ann in his URECA project. In this project, new SMH such as silicone-tin, silicone-wax as well as copper sulphate in sponge were tested for their shape memory response and characterisation. Various samples of the new SMHs were fabricated and tested for its shape memory effect. These new SMHs exhibit shape memory phenomenon by being able to be fixed at a temporary shape and to recover to its original shape in different stimulus. These shape memory phenomenon were able to be explained by means of its characterization such as Differential Scanning Calorimeter (DSC) as well as Scanning Electron Microscope (SEM) tests. Most notably, silicone-tin was confirmed to be able to recover by cooling, which is currently not presented in any scientific research paper. All these properties and findings are demonstrated and presented in this report.